HUBUNGAN PERSEPSI DUKUNGAN ORANG TUA DENGAN PENGUASAAN KOSAKATA ANAK USIA 6-7 TAHUN - Zahrina Amelia (unprimdn.ac.id, 2020)
This correlational research aims to see the relation of perception of parent support to the mastery of vocabulary 6-7 years old in South Jakarta. The research method used is correlational research, with the subject of this study a South Jakarta, with a sample 120 children. Research carried out by the technique of collecting the data through the survey with the help of a questionnaire. Mastery of the vocabulary of children covers vocabulary ( 1) active-productive that use the word, and (2) passive-receptive that understand the meaning of the word. Perception of the Support Parents are the views of children on assistance or support social were given a parent to a child , includes (1) support the emotional , (2) support informational, (3) instrumental. The Data analysis technique in this research is quantitative data analysis. Results Show that there is a significant correlation between perception of parent support with vocabulary mastery with coefficient value of determination 71%. These results imply that there is a relationship of perception of parent support and social ability to vocabulary mastery.